A combined matrix-isolation infrared spectroscopy and MO study of 1-amino-2-propanol - Cacela, Constança (2001)
Vibrational spectra of 1-amino-2-propanol (1AP) isolated in argon and krypton matrices at 14 K and of the pure liquid at room temperature were recorded and interpreted on the basis of ab initio MO calculations undertaken at the HF-SCF and MP2 levels of theory. For the first time, five different conformational states of monomeric 1AP could be experimentally observed and their vibrational signatures obtained. The observed conformers were found to correlate well with the most stable forms predicted by the MP2 calculations, the first and second lowest energy forms corresponding to conformers which exhibit a considerably strong intramolecular OH...N hydrogen bond (gG'g and g'Gg'), while the less abundant forms observed in the matrices (tG't, g'G't and tG'g') are characterized by having a relatively weak intramolecular NH...O bond. These results were reinforced by infrared solution studies of the compound in tetrachloroethylene. The experimental data obtained for the pure liquid, where OH...N intermolecular hydrogen bonding dominates, indicate that the preferred conformation of the monomeric unit within the aggregates is similar to conformer tG't.